PERAN KEPALA SEKOLAH SEBAGAI MANAJER DALAM MENINGKATKAN MUTU PENDIDIKAN BERBASIS NILAI-NILAI PANCASILA: STUDI ULASAN KEPUSTAKAAN SISTEMATIS - Nasution, Suhailah Haya; Manik, Siti Afiqa Rahmah; Barus, Dhea Ananda Br; Eviana, Tania (Universitas Negeri Medan, 2024)
This research aims to illustrate the principal’s role as a manager in enhancing the quality of education grounded in Pancasila values. The study adopts a library research method employing a Systematic Literature Review (SLR) approach to examine a range of relevant scholarly sources. The findings indicate that school principals hold a crucial role in planning, organizing, implementing, and supervising educational processes to foster a learning environment that is both high in quality and rich in character. Beyond administrative duties, principals also act as moral leaders who embed Pancasila principles into the school’s culture. Core values such as cooperation, honesty, responsibility, and justice serve as the foundation for character development, teacher competence improvement, and better student learning outcomes. Consequently, the managerial roles performed by principals, when grounded in professionalism and Pancasila values, contribute to achieving an education system that is excellent, character-oriented, and sustainable.